PENGARUH DEWAN KOMISARIS INDEPENDEN DAN KEBERAGAMAN GENDER DEWAN DIREKSI TERHADAP PROFITABILITAS DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR INFRASTRUKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2021-2023) - Ramadhani, Indira Putri; Yuliusman, Yuliusman; Ridwan, Muhammad (Magister Ilmu Akuntansi Universitas Jambi, 2025)
This purpose of this research was to determine effect of board independent commissioners and gender diversity of the board of directors on profitability, with firm size as a moderating variable, in infrastructure companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The study employs purposive sampling in determining the research sample, based on specific predetermined criteria. This study used a sample of 59 companies. The data used is secondary data. The analysis method used in this study is Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4.0 software. The analysis was conducted in two stages, the outer model and the inner model. The results showed that independent commissioners do not have a significant effect on company profitability. Gender diversity of the board of directors and firm size both have a significant effect on profitability. The moderation test results show that firm size does not moderate the relationship between independent commissioners or gender diversity of the board of directors and profitability.